A study on the isokinetic strength of knee extensors and flexors in sabre athletes - Chen, H.; Jiang, Y. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction Isokinetic strength testing systems are a typical method of accurately testing the strength of athletes. However, few tests have been designed for saber athletes. This is unfortunate as the strength of the knees is a very important factor for saber athletes. Through an isokinetic strength study on knee extensors and flexors of Beijing Sabre Team athletes, the characteristics of knee strength were analysed with the aim of providing a scientific basis for future specific training.